Pemecahan Saham Dan Pertumbuhan Laba - Anggraini, Wahyu; Mareta, Sigit (Universitas Mercu Buana, 2021)
Stock splits have no economic value for shareholders but often the market reacts to these announcements. This study purpose to determine whether stock split brings information about the company's earning growth. The population used in this study were companies that did stock split on the Indonesia Stock Exchange for the 2015-2016 period. The earning that will be observed is the company's earning for the 2013-2014 period and 2017-2018 period. The sampling technique used in this study was purposive sampling. The analysis technique used in this research is descriptive statistics and the paired samples test. The data analysis method used in this study will use the SPSS application. The results of this study indicate that before and after the stock split there is no significant earning growth